Anomalistics, Pseudo-Science, Junk Science, Denialism: Corollaries of the Role of Science in Society - Bauer, Henry (Journal of Scientific Exploration, 2014)
<span style="font-size: 11.0pt; mso-bidi-font-size: 10.0pt; font-family: "Times New Roman"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Recent decades have seen a number of public disputes over scientific anomalies and unorthodoxies, typically framed as science versus pseudo-science. This Essay suggests historical and intellectual context for these controversies. The main point: There is no universally applicable, objective, impartial formula for distinguishing good science from bad science or real science from pseudo—the devil is always in the details. Anomalies and unorthodoxies are defined implicitly by the contemporary state of the art in mainstream science; “pseudo-science” is a pejorative aimed at non-mainstream claims in defense of the authority of established, mainstream science. WWII was a game-changer: In its aftermath, science achieved unprecedented influence over public policies. As the stakes became high, “pseudo-science” seemed no longer a sufficiently powerful pejorative and was superseded by charges of “junk science” and “denialism.”